A micro-spray-based high-throughput screening system for bioplastic-degrading microorganisms. Issue 15 (14th July 2021) - Shin, Giyoung; Park, Seul-A.; Koo, Jun Mo; Kim, Minsun; Lee, Minkyung; Jegal, Jonggeon; Hwang, Sung Yeon; Park, Jeyoung; Oh, Dongyeop X.
Abstract : A facile and efficient method for bioplastic degrading microorganism screening based on a micro-spray system is developed. The potential of this approach was validated by isolating various bioplastic degrading bacteria from the activated sludge. Abstract : Designing efficient plastic-digesting microorganisms is necessary to accelerate the decomposition of biodegradable plastics leaking into outer environments. However, screening of microorganisms for hydrophobic plastics is labor-intensive and time-consuming. Herein, a high-throughput, straightforward micro-spray-based screening system is presented; the whole process only takes 1–5 days using a minimal amount of polymers. Bioplastic microparticles sprayed on an agar plate share a large interface with microorganisms, and therefore their discovery is readily recognizable. This method inspires finding new microorganisms that digest conventional plastics known as non-degradable plastics.